2017
DOI: 10.14260/jemds/2017/1284
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Cross-Finger Flap Versus Split-Thickness Skin Graft for Resurfacing of Soft Tissue Loss in Fingertip Injury

Abstract: BACKGROUNDDifferent types of Fingertip injuries are found in human population and different modalities of treatment options are available. Results of the treatment vary according to the mode of treatment. In our institute, we prefer cross-finger flap coverage for composite tissue loss of fingertip defect. The aim of the study is to find out long-term result of cross-finger flap in comparison with STSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(6 reference statements)
1
1
0
Order By: Relevance
“…Jeyakumar and Kumar (2019) also found similar finding where right hand digital injury occurred in 86 (71.08%) patients and only 35 (28.92%) patients had injury in the left hand, with a total 121 cases. [10][11][12] Those findings were similar to present study. Among the current study subjects, more than one third (37.5%) of the patients (15 out of 40) were found injury of index finger followed by 8 (20.0%) in middle finger, 6 (15.0%) in ring finger, 3 (7.5%) in little finger and 1 (2.5%) in thumb.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Jeyakumar and Kumar (2019) also found similar finding where right hand digital injury occurred in 86 (71.08%) patients and only 35 (28.92%) patients had injury in the left hand, with a total 121 cases. [10][11][12] Those findings were similar to present study. Among the current study subjects, more than one third (37.5%) of the patients (15 out of 40) were found injury of index finger followed by 8 (20.0%) in middle finger, 6 (15.0%) in ring finger, 3 (7.5%) in little finger and 1 (2.5%) in thumb.…”
Section: Discussionsupporting
confidence: 92%
“…This is probably due to right hand dominance in most of the people. Panda (2017) reported that out of 72 patients of his study, 53 (73.61%) patients had injury in the right hand and 19 (26.39%) had in the left hand. Jeyakumar and Kumar (2019) also found similar finding where right hand digital injury occurred in 86 (71.08%) patients and only 35 (28.92%) patients had injury in the left hand, with a total 121 cases.…”
Section: Discussionmentioning
confidence: 86%